2001
DOI: 10.1143/jjap.40.5819
|View full text |Cite
|
Sign up to set email alerts
|

Raman Scattering in (1-x)Pb(Zn1/3Nb2/3)O3–xPbTiO3 Mixed Crystal System II

Abstract: The temperature-concentration dependences of the Raman spectra in the high-temperature region above the Burns temperature and the electron diffraction at room temperature were investigated in the (1 − x)Pb(Zn 1/3 Nb 2/3 )O 3 -xPbTiO 3 mixed crystal system. It was found that in the concentration range below x = 0.8, the Raman active modes exist in the cubic phase and the intensities of the Raman lines in the cubic phase decrease with increasing temperature. A finite region where the Raman active modes are obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 17 publications
4
23
0
Order By: Relevance
“…If our conjecture is in the right, the Raman scattering would become a conventional tool for the PNR, for example, the Burns temperature can be determined by the Raman scattering. Indeed, we have already reported the region in which Raman modes exist in the cubic phase on the temperature-concentration phase diagram of PZN-xPT [15]. Reported results of the IR spectrum and hyper Raman scattering in Pb(Mg 1/3 Nb 2/3 )O 3 (PMN) also seem to support our conjecture [16,17].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…If our conjecture is in the right, the Raman scattering would become a conventional tool for the PNR, for example, the Burns temperature can be determined by the Raman scattering. Indeed, we have already reported the region in which Raman modes exist in the cubic phase on the temperature-concentration phase diagram of PZN-xPT [15]. Reported results of the IR spectrum and hyper Raman scattering in Pb(Mg 1/3 Nb 2/3 )O 3 (PMN) also seem to support our conjecture [16,17].…”
Section: Introductionsupporting
confidence: 79%
“…On the contrary, we proposed that the Raman modes in PZN-xPT arise primarily due to the polar ordering it self on the basis of experimental results of the electron diffraction and Raman scattering of the PZN-xPT system in full concentration range [15]. If our conjecture is in the right, the Raman scattering would become a conventional tool for the PNR, for example, the Burns temperature can be determined by the Raman scattering.…”
Section: Introductionmentioning
confidence: 94%
“…Figure 5 shows temperature evolutions of the reduced (corrected by Bose-Einstein population factor) unpolarized Raman spectra of 0.5 PMN-0.5 PT and 0.36 PMN-0.64 PT crystals. Similarly as in other complex perovskites, such as disordered PST and PIN, as well as PZN-PT [14][15][16][17][18][19], the first order Raman spectrum appears in PMN-PT single crystals within the cubic paraelectric phase. This spectrum, forbidden for Pm3m space group, originates from nanoregions of different local symmetry.…”
Section: Resultsmentioning
confidence: 54%
“…On the other hand, the (1/2, 1/2, 1/2) superlattice diffractions (F-spots) have been observed in PZN-xPT by electron diffraction measurement. It was reported that the chemical order structure characterized by F-spots vanished at x F ∼ 0.20 [12]. The existence of such a structure indicates an inhomogeneity of the cubic phase and should be related directly and/or indirectly to the relaxor's nature.…”
Section: Resultsmentioning
confidence: 97%